Genetic divergence analysis in ajowan [Trachyspermum ammi (L.) Sprague]Genetic divergence analysis in ajowan [Trachyspermum ammi (L.) Sprague] - Umesh Kumar Jain, R V Paliwal (Journal of Spices and Aromatic Crops, 2006)
Fifty eight genotypes of ajowan (Trachyspermum ammi) were subjected to multivariate analysisusing D2 statistics at Pratapgarh (Rajasthan). The characters studied were days to 50%flowering, days to maturity, umbels plant-1, umbellets umbel-1, 1000-seed weight, fatty oilcontent of seed and seed yield plant-1. The study indicated that the genotypes grouped intoseven clusters depending on similarities of their D2 values and lack of parallelism betweengenetic and geographic diversity. The inter cluster D2 values ranged from 16.41 to 45.23,suggesting considerable diversity among the groups of the genotypes. Among the sevencharacters studied for genetic divergence, fatty oil contributed the maximum accountingfor 56.29% of total divergence followed by seed yield plant-1. Based on cluster means, char-acters such as umbels plant-1 and umbellets umbel-1 were major factors of differentiationamong genotypes, which may be taken into account while selecting parents for hybridiza-tion programmes.